The relationship between dental caries and nutritional status of 5-years-old Thai children - บุญธรรม, กันยา; ลีละศิธร, ศรึสุดา (Thai Dental Public Health Journal, 2016)
This study aimed to investigate the relationship between dental caries and nutritional status of 5-years-old Thai children. The analysis used data from the 7th National Oral Health survey in 2012. Sampling from 4 regions, 4 provinces per regions, include Bangkok. Total number was 17 provinces. The status of dental caries was investigated by using World Health Organization criteria and recorded as the total number of teeth. For nutritional status, weight and height for age of each child were assessed and interpreted with the criterion defined by Bureau of Nutrition, Department of Health. This study operated between December 2015 and March 2016. The results showed 78.5 percent of 2,626 children had dental caries, 35.8 percent had dental caries 1-4 teeth and 42.7 percent had dental caries more than 4 teeth. Nutritional status which measured by weight for age found that these 5-years-old children were under, normal and over weight 19.6 %, 70 % and 10 % respectively. In addition, the height for age measurement showed that the prevalence of short stature, normal height and tall stature were 13.0 %, 78.8 % and 3.4 % respectively. Children having dental caries more than 4 teeth had average weight and height significantly less than children having dental caries 1-4 teeth or having caries free (p <.001). Moreover, children having dental caries more than 4 teeth could be 1.4 times less weight than caries-free children (OR = 1.4, 95% CI 1.1-1.9) and 1.5 times shorter than caries-free children (OR = 1.5 95% CI 1.1-2.0).